Sosialisasi Pemanfaatan Aplikasi Kuesioner ATD Dan Likert Untuk Penelitian Survei Kuantitatif - Goenawan, Stephanus Ivan; Vivi Triyanti; Hutahaean, Hotma Antoni; Wibawa Prasetya; silalahi, Agustinus (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2024)
Using technology in quantitative research is increasingly important to improve the efficiency and accuracy of data collection. This community service activity aims to socialize the use of questionnaire applications based on the Data Weigher Analysis (DWA) and Likert methods that can be used in quantitative survey research. Socialization is carried out to researchers, academics, and students involved in survey-based research to facilitate understanding and skills in designing, distributing, and analyzing questionnaires digitally. Through this activity, participants are given direct training on using the application, the advantages of the DWAand Likert methods in measuring quantity values into quality, and efficient and accurate data processing. The evaluation results showed that participants had increased understanding and skills in utilizing the questionnaire application, which is expected to support more effective quantitative research in the future. Thus, this activity contributes to increasing researchers' capacity to conduct modern and technologybased quantitative surveys.